Norepinephrine was superior in death risk reducing and hemodynamics compared to dopamine in treatment of patients with septic shock - Lu Xudong (Pteridines, 2021)
To investigate the clinical effects of norepinephrine versus dopamine in treatment of septic shock by pooling the data form open published clinical trials.